2018
DOI: 10.1021/jacs.7b11712
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Change-Induced Fluorescence of Bovine Serum Albumin–Gold Complexes

Abstract: We report new findings on the red fluorescent (λ = 640 nm) bovine serum albumin (BSA)-gold (Au) compound initially described by Xie et al. (J. Am. Chem. Soc. 2009, 131, 888-889) as Au nanoclusters. The BSA-Au compounds were further reducible to yield nanoparticles, suggesting that these compounds were BSA-cationic Au complexes. We examined the correlations between BSA conformations (pH-induced as well as denatured) and the resulting fluorescence of BSA-Au complexes, to understand the possible cationic Au bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
93
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(112 citation statements)
references
References 56 publications
5
93
0
Order By: Relevance
“…7, 4.3, 8, and 10 [8,11,12]. According to the recent paper [13], only BSA in the Aged form (pH > 10) interacting with Au ions forms the red fluorescent species (i.e., multiple chromophores such as Au-complexes and AuNCs, which are present on different binding sites of BSA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7, 4.3, 8, and 10 [8,11,12]. According to the recent paper [13], only BSA in the Aged form (pH > 10) interacting with Au ions forms the red fluorescent species (i.e., multiple chromophores such as Au-complexes and AuNCs, which are present on different binding sites of BSA).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning metal cations, four binding sites are described in albumins: N-terminal site (NTS, or "Asp fragment"), vicinity of Cys34 (the only cysteine residue in BSA that does not form disulfidic bridges), multi-metal binding site (MBS or site A) at the interface of domains I and II, and site B [15]. Two of these sites, NTS and Cys34, were examined as possible binding or nucleation sites of gold (0 or III) [13]. Based on intentional cysteine residues blocking, it was evidenced [13,15] that all cysteine residues, not specially Cys34, served as the best binding sites for gold ions in albumin.…”
Section: Introductionmentioning
confidence: 99%
“…25 The amino acid compositions of the proteins are almost similar, particularly for the binding and reduction of Au 3+ to produce the gold clusters. 26 The PL quantum yield upon visible light excitation (470 nm) was the highest in lactoferrin-Au, while the PL lifetime was the shortest. XPS also showed that the amount of Au(I) in the lactoferrindirected cluster was slightly higher than for the other clusters; indeed, Schneider et al reported the absence of Au(I) in BSAdirected Au 8 clusters.…”
Section: Resultsmentioning
confidence: 96%
“…So, after 3 h of reaction with gelatin at 60 °C under alkaline conditions, Au (III) has been reduced partially to Au (I) and Au (0) to form AuNCs. However, Au (III)–protein complex has been assigned recently by Dixon and Egusa to also contribute to the fluorescence . By virtue to the electron‐donating groups in gelatin, Au (I) as an intermediate reduced state of gold has been produced, with a further reduction to Au (0).…”
Section: Resultsmentioning
confidence: 99%